2013
DOI: 10.1371/journal.pone.0061355
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Cocaine Exposure Facilitates the Expression of Incentive Motivation and Induces Habitual Control in Rats

Abstract: There is growing evidence that mere exposure to drugs can induce long-term alterations in the neural systems that mediate reward processing, motivation, and behavioral control, potentially causing the pathological pursuit of drugs that characterizes the addicted state. The incentive sensitization theory proposes that drug exposure potentiates the influence of reward-paired cues on behavior. It has also been suggested that drug exposure biases action selection towards the automatic execution of habits and away … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
74
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(87 citation statements)
references
References 79 publications
12
74
1
Order By: Relevance
“…Indeed, a recent transfer study found that Pavlovian cues associated with passive intravenous cocaine delivery have the ability to provoke cocaine seeking in rats (LeBlanc et al, 2012). Furthermore, studies using a food-motivated version of the transfer task have shown that rats given repeated exposure to psychostimulants exhibit heightened levels of cuetriggered food seeking (Leblanc et al, 2013a;LeBlanc et al, 2013b;Saddoris et al, 2011;Wyvell and Berridge, 2001), suggesting that these drugs cause long-lasting alterations in the neural substrates of Pavlovian incentive motivation. The current findings indicate that this behavioral influence of Pavlovian learning critically depends on cholinergic signaling through muscarinic and nicotinic receptors, suggesting that drug-induced adaptations in the cholinergic system may contribute to compulsive drug seeking by augmenting the influence of Pavlovian cues.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a recent transfer study found that Pavlovian cues associated with passive intravenous cocaine delivery have the ability to provoke cocaine seeking in rats (LeBlanc et al, 2012). Furthermore, studies using a food-motivated version of the transfer task have shown that rats given repeated exposure to psychostimulants exhibit heightened levels of cuetriggered food seeking (Leblanc et al, 2013a;LeBlanc et al, 2013b;Saddoris et al, 2011;Wyvell and Berridge, 2001), suggesting that these drugs cause long-lasting alterations in the neural substrates of Pavlovian incentive motivation. The current findings indicate that this behavioral influence of Pavlovian learning critically depends on cholinergic signaling through muscarinic and nicotinic receptors, suggesting that drug-induced adaptations in the cholinergic system may contribute to compulsive drug seeking by augmenting the influence of Pavlovian cues.…”
Section: Discussionmentioning
confidence: 99%
“…For example, as noted above, specific transfer effects are impervious to outcome devaluation, suggesting that the cuing effects of stimuli do not require that the consequences of the invigorated response be a current goal. Furthermore, transfer effects appear to grow under conditions that favor habitual responding, such as following extended training (Holland 2004) or drug exposure (Saddoris et al 2011;LeBlanc et al 2013), again providing evidence of a dissociation between the ability of stimuli to invigorate responding and an evaluative process concerned with the consequences of that responding.…”
Section: Pavlovian Incentives and Pathologies Of Decision Makingmentioning
confidence: 99%
“…Immediately after each injection the rats were placed in the behavioral chamber used for initial training for 45 min. This cocaine administration protocol was previously shown to support locomotor sensitization and facilitate the expression of the PIT effect (LeBlanc et al, 2013b). Rats remained undisturbed in their home cages for 8 days before further behavioral testing.…”
Section: Cocaine Administrationmentioning
confidence: 99%